“InMotion”—Mixed physical exercise program with creative movement as an intervention for adults with schizophrenia: study protocol for a randomized controlled trial - Poikonen, Hanna; Duberg, Anna; Eriksson, Mats; Eriksson-Crommert, Martin; Lund, Majja; Möller, Margareta; Msghina, Mussie (Frontiers in Human Neuroscience, 2023)
Background: Schizophrenia is among the world's top ten causes of long-term disability with symptoms that lead to major problems in social and occupational functioning, and in self-care. Therefore, it is important to investigate the efficacy of complementary treatment options for conventionally used antipsychotic medication, such as physical training, and psychosocial interventions. Objective: To combine aerobic and strength training with cognitive, emotional and social stimulation in one intervention for people with schizophrenia and test the feasibility and effects of this intervention. Methods: The study is a mixed-method randomized controlled trial to evaluate the effects of a 12-week intervention for adults with schizophrenia. The treatment group (30 participants) will receive the intervention in addition to standard care and the control group (30 participants) only standard care. The intervention consists of 24 biweekly sessions with a duration of 60 minutes. The pre-test (2-4 weeks prior to the intervention) and post-test (week 12) include clinical measure (PANSS), quality of life, social performance, movement quantity, brain function and eye tracking measures. In addition, a treatment subgroup of 12-15 participants and their family member or other next of kin will complete a qualitative interview as a part of their post-test. Two follow-up tests, including clinical, quality of life, brain function and eye tracking will be made at 6 months and 12 months from the completion of the intervention to both study groups. The primary outcome is change in negative symptoms. Secondary outcome measures include general and positive symptoms, quality of life, social performance, movement quantity, brain function and eye tracking. Explorative outcome includes patient and family member or other next of kin interview. Results: Pilot data was collected by June 2023 and the main data collection will begin in September 2023. The final follow-up is anticipated to be completed by 2026. Conclusions: The InMotion study will provide knowledge on the feasibility, efficacy, and experiences of a novel intervention for adults with schizophrenia. The hypothesis is that regular participation in the intervention will reduce clinical symptoms, normalize physiological measures like brain activation, and contribute to new active habits for the participants. Trial Registration: Clinical Trials (number NCT05673941).